EFEKTIVITAS SISTEM ONLINE SINGLE SUBMISSION RISK BASSED APROACH (OSS RBA) DALAM PENDAFTARAN NIB DI DINAS PENANAMAN MODAL DAN PELANAN TERPADU SATU PINTU PROVINSI BALI - Yunia Putri, Ni Kadek; Udytama, I Wayan Wahyu Wira (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Complex bureaucracy and slow licensing processes hinder growth and investment in Indonesia. Although the government has introduced the OSS RBA policy to improve the licensing system, challenges remain, including limited understanding and technical difficulties, as well as inadequate IT infrastructure. This study identifies the need for education, training, technical assistance, and enhanced coordination between local governments and the OSS RBA platform administrators to address these issues. An empirical legal research method was used, with data collected through observation, interviews, and document studies. The findings are expected to provide insights into the effectiveness of OSS RBA in NIB registration at the DPMPTSP of Bali Province and the challenges faced in its implementation.